Peningkatan Kemampuan Berpikir Kritis dan Sikap Kreatif Siswa Kelas V Melalui Model Pembelajaran PJBL-STEM Berbantuan Media Aplikasi Belajar Siklus Air (ABSA) pada Mata Pelajaran IPA di Sekolah Dasar - Azam Mirfaka; Farida Nur Kumala; Sriatun Sriatun; Azam Mirfaka; Farida Nur Kumala (Universitas Negeri Malang, 2023)
Abstract: This research is motivated by the results of observations which show that students' critical thinking skills and creativity are still low. The purpose of this study was to determine the application of PjBL-STEM learning assisted by Water Cycle Learning Application (ABSA) media in order to improve the critical thinking skills and creativity of fifth grade students. The type of research used was Collaborative PTK with 34 research subjects. Data collection techniques in the form of observation, tests and documentation. This research is said to be successful if fifth grade students can achieve success indicators greater than 75 percent or with a score of greater than 75 for critical thinking skills and obtain an average score from the observations made reaching the